A Novel Drinking Aid for Elerly Patients- a qualitative study - Merriman, Charlotte (2013)
Background: Dehydration occurs when the body loses fluids at a greater rate than it takes in. For some patients, achieving an acceptable fluid balance is difficult without assistance and they rely on interventions by health professionals. Literature indicates that dehydration has long been a well researched area; however, there is still an apparent lack of knowledge throughout healthcare staff and evidence from more recent publications indicate that this remains a prevalent issue within nursing care. Aim: To undertake an acceptability study of the Hydrant with elderly inpatients. Methods: A qualitative study was undertaken to explore the acceptability and ease of use of a ‘novel’ hands free drinking aid called the Hydrant. After experiencing difficulties in recruitment, a revised study was designed. This used a sample of 20 participants from a Health Care of the Older Person ward. Structured face to face interviews were conducted with the use of a recording sheet. The interview compromised of open and closed questions as well as rating scales. These were designed to ascertain the participants’ normal drinking habits as well as their views on the acceptability and ease of use of the Hydrant. Findings: The research gave an interesting insight into what and when patients usually drank. When initially presented with the Hydrant participants gave many positive comments however when the opportunity arose to use the Hydrant participants experienced great difficulty. After receiving some training they found the Hydrant easier to use however many still struggled. Conclusion: The study outcomes showed that the Hydrant was not a usable product for the elderly who had either poor sucking ability and/or poor bite. The Hydrant was also poor in terms of acceptability, 90% of participants preferred to use a traditional water jug instead of the Hydrant.